Response of vincristine, melphalan, cyclophosphamide and prednisolone in refractory multiple myeloma - Kabir, AL; Rahman, MJ; Begum, M; Dipta, TF; Baqui, MN; Aziz, A; Rahman, F; Debnath, RC; Habib, MA (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):114-119 The abstract of this article is available on the PubMed website